The Legal Mechanisms of State Support for Agribusiness Through the Introduction of Virtual Asset Technologies: Ukraine’s Experience in the Global Context - Kovalchuk, Inna; Melnyk, Victoria; Novak, Tamara; Pakhomova, Anna; Nastina, Olga (European Journal of Sustainable Development, 2025)
The article examines innovative approaches to state support for agribusiness through the implementation of virtual asset technologies in the Ukrainian legal field, taking into account international experience. The relevance of the topic is due to the need to modernize the existing mechanisms for financing the agricultural sector in the context of the digital transformation of the economy and the development of the global crypto-asset market. The authors analyzed the current state of legal regulation of virtual assets in Ukraine, in particular in the context of the Law of Ukraine "On Virtual Assets" and its implementation. Also, it was outlined the main problems and obstacles to the introduction of innovative financial instruments in the agricultural sector including: instability of the regulatory framework, insufficient integration of digital solutions into state support programs, as well as low technological readiness of small and medium-sized agricultural producers. The authors studied the international experience of using blockchain technologies to support the agricultural sector in countries such as the USA, Australia, Singapore and the countries of the European Union. In particular, the authors paid attention to the analysis of legal models of tokenization of agricultural assets and the use of smart contracts to optimize the processes of state subsidies. Based on the analysis, the authors proposed a comprehensive model of integration of virtual asset technologies into the mechanisms of state support for agribusiness in Ukraine. The key elements of this model are: the creation of special legal regimes for agricultural tokens and NFTs, the formation of infrastructure for the digital interaction of farmers with state institutions, the implementation of blockchain solutions for the transparent distribution of subsidies, as well as the development of a legal framework for agricultural digital cooperatives. The authors substantiated the need to amend the legislation of Ukraine, in particular the Law of Ukraine "On State Support of Agriculture of Ukraine", the Tax Code and relevant regulations on virtual assets. Also, the authors identified the potential risks and advantages of the proposed innovations for both agricultural producers and the state. The results of the research are of theoretical and practical importance for the formation of state policy in the field of the agro-industrial complex of Ukraine, taking into account the global trends in digitalization and the use of distributed ledger technologies to ensure the efficiency, transparency and accessibility of state support for agribusiness. Keywords: virtual assets, blockchain, smart contracts, state support for agriculture, tokenization of agricultural assets, agricultural sector, digital transformation.